Safety Evaluation of repeated oral administration of Gemifloxacin in Broiler Birds - Gohel, R.H.; Sadariya, K.A.; Maradiya, J. J.; Thaker , A.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Gemifloxacin is a fourth generation fluoroquinolone drug having broad-spectrum and good antibacterial activity at low plasma/tissue concentration. The present study was designed to investigate safety of gemifloxacin @ 10 mg/kg body weight after repeated oral administration at 24 hr interval for 5 days in 6 broiler birds of 5-6 week age. It was found safe based on non-significant alteration in haematological (Hb, PCV, TEC and TLC) and serum biochemical (AST, ALT, ACP, ALP, LDH, creatinine, total bilirubin and uric acid) parameters that were evaluated before and at 24 hourly interval for 5 days during treatment.
Keywords: Gemifloxacin; Broiler birds; Haematology; Serum Biochemistry